1994
DOI: 10.1113/jphysiol.1994.sp020449
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of endothelium‐derived hyperpolarizing factor as a cytochrome P450‐derived arachidonic acid metabolite in mammals.

Abstract: 1. In addition to nitric oxide (NO) and prostacyclin (PGJ2) an as yet unidentified endothelium-derived hyperpolarizing factor (EDHF) contributes to the dilator effect of bradykinin in different vascular beds. We have investigated the nature and mechanism of action of this factor in freshly isolated bovine and porcine coronary artery segments which were preconstricted with the thromboxane mimetic U46619 (9,11-dideoxy-lla, 9ac-epoxymethano-prostaglandin F2a, 10-30 nM). 2. The concentration-response curve of brad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
306
6

Year Published

1996
1996
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(337 citation statements)
references
References 22 publications
22
306
6
Order By: Relevance
“…The mono-oxygenases themselves seem to be located primarily within the endothelium (Abraham et al, 1985) and endothelial cells are capable of synthesizing EETs (see Harder et al, 1995). These findings, together with the ability of cytochrome P450 inhibitors, such as proadifen and clotrimazole, to attenuate EDHF-mediated vasodilatation, support the view that EDHF is an arachidonic acid metabolite derived via a cytochrome P450-dependent mono-oxygenase (Fulton et al, 1992;Bauersachs et al, 1994;Hecker et al, 1994;Lischke et al, 1995).…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…The mono-oxygenases themselves seem to be located primarily within the endothelium (Abraham et al, 1985) and endothelial cells are capable of synthesizing EETs (see Harder et al, 1995). These findings, together with the ability of cytochrome P450 inhibitors, such as proadifen and clotrimazole, to attenuate EDHF-mediated vasodilatation, support the view that EDHF is an arachidonic acid metabolite derived via a cytochrome P450-dependent mono-oxygenase (Fulton et al, 1992;Bauersachs et al, 1994;Hecker et al, 1994;Lischke et al, 1995).…”
Section: Introductionsupporting
confidence: 67%
“…Certain metabolites of arachidonic acid such as 5,8,11,[12][13][14] can relax blood vessels (Pfister et al, 1991;Gebremedhin et al, 1992;Rosolowsky & Campbell, 1993;Hecker et al, 1994) and activate potassium (K) channels in vascular smooth muscle cells (Gebremedhin et al, 1992;Hu 1 Author for correspondence. & Kim, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…17) For example, Ca 2+ -activated K + channels may be involved in bradykinin-induced dilation of bovine and porcine coronary arteries. 11) Other studies of rabbit cerebral arteries 3) have reported that GB inhibited hyperpolarization in response to acetylcholine. This study did not examine the effect of other K + -channel subtype inhibitors in bFGF-induced hyperpolarization, and therefore we could not exclude the possibility of their involvement in this response.…”
Section: Discussionmentioning
confidence: 99%
“…The EETs induce vasodilation by opening Ca 2+ -activated K + (K Ca ) channels on the vascular smooth muscle cell, which increases K + influx and hyperpolarizes the cell membrane [19,46,50,51,54,[64][65][66]. It is thought that this hyperpolarization decreases Ca 2+ influx through voltage-sensitive Ca 2+ channels, ultimately leading to a decrease in intracellular [Ca 2+ ] with subsequent vasorelaxation, as shown in Fig.…”
Section: Vasomotor Actions Of Eetsmentioning
confidence: 99%